Investigation of Soil Physiochemical Properties Effects on Soil Compaction for a Long Year Tilled Farmland - Yared Seifu Woldeyohannis; Someshakher S Hiremath; Simie Tola; Amana Wako (Applied and Environmental Soil Science)
In many parts of the world, the earth has been heavily compacted as a result of large farm equipment. For soil compaction, the main constituent factors were soil physiochemical properties such as soil texture, moisture content, electrical conductivity, cation exchange capacity, total organic carbon, organic matter, total nitrogen, and soil pH directly and indirectly. This article addressed the causes and effects of soil compaction, operating parameters, and soil physicochemical properties in the Bishoftu long year tilled farmland of Ethiopia. For the experimental test, 5 different depths (5, 10, 15, 20, and 25 cm) and fifteen sample points were selected in 0.6 ha of 60 m by 100 m farmland for taking soil compaction data. Soil samples are taken from three depth ranges (0–10, 10–20, and 20–30 cm) from farmlands for investigation of soil physicochemical properties. The maximum and minimum values of the cone index of this study were 1918.133 kPa and 864.733 kPa, respectively, by taking the average of all sample points. The soil laboratory result shows that Bishoftu farmland soil is a mixture of loam, clay loam, and sandy clay loam with 47.33% of sand, 25.67% of clay, and 27% of silt. The maximum and minimum percentages of soil moisture values were 27.02 and 21.46 at 0–10 cm and 20–30 cm depth, respectively. Total organic carbon, organic matter, and total nitrogen exhibit positive relationships with depth and soil compaction. The correlation analysis indicates soil pH, electric conductivity, percentage of sand, cation exchange capacity, organic matter, and total nitrogen were among soil physiochemical parameters that are positively correlated with soil compaction. Furthermore, the percentage of clay, percentage of silt, and total organic carbon (p≤0.05) are negatively correlated with soil compaction in soil samples.